2021
DOI: 10.1080/00207543.2021.1969462
|View full text |Cite
|
Sign up to set email alerts
|

Digitalisation and servitisation of machine tools in the era of Industry 4.0: a review

Abstract: Machine tools play a pivotal role in the manufacturing world since their performance significantly affects the product quality and production efficiency. In the era of Industry 4.0, machine tools are expected to have a higher level of accessibility, connectivity, intelligence, adaptivity, and autonomy. With the rapid development and application of various Industry 4.0 technologies, digitalisation and servitisation of machine tools have become a new research trend. However, few review articles on the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(22 citation statements)
references
References 186 publications
0
22
0
Order By: Relevance
“…In the first step, a literature review identified the gaps in previous studies; the review uncovered four key themes and provided insights to guide a follow-up empirical investigation and discussion of the case results. A literature review is suitable for investigating and exploring the most current application developments in Industry 4.0 and finding their future potential (Liu, Zheng, and Xu, 2021;Winkelhaus and Grosse, 2019;Zheng et al, 2020). The second step is a case study investigation of AGV implementation within a manufacturing company aiming to develop a system design model that can be used in smart, flexible manufacturing systems.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the first step, a literature review identified the gaps in previous studies; the review uncovered four key themes and provided insights to guide a follow-up empirical investigation and discussion of the case results. A literature review is suitable for investigating and exploring the most current application developments in Industry 4.0 and finding their future potential (Liu, Zheng, and Xu, 2021;Winkelhaus and Grosse, 2019;Zheng et al, 2020). The second step is a case study investigation of AGV implementation within a manufacturing company aiming to develop a system design model that can be used in smart, flexible manufacturing systems.…”
Section: Methodsmentioning
confidence: 99%
“…The selected databases provide access to articles related to the topic under investigation and have been used in similar studies (Ghobakhloo et al, 2021;Liu, Zheng, and Xu 2021;Winkelhaus and Grosse, 2019;Zheng et al, 2020). Duplicate results were omitted, and 75 articles were included in the review after reading each article.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In the continuous iteration of the above three steps, the samples with large loss values are regarded as samples with low quality, and they are deleted from the training datasets by assigning them a small weight or 0 to reduce or avoid the negative impact of such samples on the performance of the classifier. Meanwhile, in the self-paced learning model shown in (1), age parameters 𝜆 are hyperparameters that need to be set for self-paced learning. However, the age parameter setting of self-paced learning usually requires priori knowledge of data.…”
Section: B Self-paced Learningmentioning
confidence: 99%
“…ITH a prevailing development of the manufacturing industry towards digitization and servitisation [1], datadriven intelligence with advanced analytics has become one of the key enablers for the intelligent manufacturing process, such sampling methods such as Easyensemble [17] and clustering analysis and instance selection [18]. At present, data-level methods have been widely applied to intelligent fault diagnosis.…”
Section: Introductionmentioning
confidence: 99%